Diagnostic Criteria for Metabolic Syndrome in High-Altitude Regions: A Systematic Review - Claudia Beatriz Villegas-Abrill; Rubén Vidal-Espinoza; Rossana Gomez-Campos; Vladimiro Ibañez-Quispe; Charles Mendoza-Mollocondo; Sara Ruth Cuentas-Yupanqui; José Fuentes-López; Camilo Urra-Albornoz; Marco Cossio-Bolaños (Medicina, 2022)
Background and Objectives: Metabolic syndrome (MS) has many risk factors that are important to investigate in populations living at sea level and in high-altitude geographic regions. The aim was to identify the components of MS that cross-sectional studies use to assess in adult populations residing in high-altitude regions. Materials and Methods: A systematic review study was conducted. The Pubmed database was used. The search for original articles (cross-sectional) was performed from January 2013 to December 2020. The procedure was carried out by two researchers. The keywords used were metabolic syndrome, adults, and altitude regions. The search strategy considered the components of the PICOS tool. Results: Ten cross-sectional studies were identified in the Pubmed database from 2014 to 2020. Altitude levels varied between countries and regions, from 2060 to 4900 m above sea level. Three studies were conducted in both China and Peru, two studies in Ecuador, and one in Bolivia and India. The age ranges studied were from 18 to ~80 years of age, approximately. The components used to assess MS in most studies (between 9 to 10 studies) were body mass index (BMI), waist circumference (WC), blood pressure (BP), triglycerides (TG), high-density lipoproteins (HDL) and serum glucose (SG). Conclusions: This systematic review verified that the most commonly used domains in adult populations in various moderate- and high-altitude regions of the world are BMI, WC, BP, TG, HDL, and SG. These results suggest that in order to evaluate and/or investigate MS in subjects residing in high-altitude populations, at least four diagnostic domains should be considered in their protocols.